PJMHS 2021
DOI: 10.53350/pjmhs211551504
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Causes of Pericardial Effusion in Patients Presenting to Emergency Department with Dyspnea

Abstract: Objective: To determine the frequency and causes of pericardial effusion in patients presenting to emergency department with dyspnea. Study Design: Prospective/Observational study Place & Duration:Cardiac Centre, Pakistan Institute of Medical Sciences (PIMS),Islamabad for duration of one year from January 2019 to Dec 2019. Methods: A total 220 patients of both genders with ages above 20 years presented with dyspnea were enrolled in this study. Patients detailed medical history was recorded after taking inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The patients belonged to the age group of 1 to 7 having mean age 45.23±7.52 years, we observed that the majority of the patients belonged to the male gender. The frequency of pericardial effusion in our study was 18 (15%), similar frequency has been reported by a study 18 which showed that 17% patients had pericardial effusion, and another study reported the prevalence of pericardial effusion 19.3% 19 .…”
Section: Discussionsupporting
confidence: 91%
“…The patients belonged to the age group of 1 to 7 having mean age 45.23±7.52 years, we observed that the majority of the patients belonged to the male gender. The frequency of pericardial effusion in our study was 18 (15%), similar frequency has been reported by a study 18 which showed that 17% patients had pericardial effusion, and another study reported the prevalence of pericardial effusion 19.3% 19 .…”
Section: Discussionsupporting
confidence: 91%